Fundraising and Philanthropy in College Unions. Issue 145 (March 2014) - De Sawal, Danielle M.; Maxwell, Daniel
Abstract : This chapter addresses ways college union professionals can establish partnerships and strategies for establishing fundraising and philanthropy initiatives within their organizations.